Unveiling the Determinant Factors Effecting the Willingness to Share Waqf Information among Malaysians - Yusuff, Noraini; Johari, Fuadah; Ishak, Nor Syahidah; Misbah, Hanim; Harun, Siti Latipah; Hasbullah, Nurul Adilah; Ahmad Musadik, Siti Hajar Salwa; Ahmad, Azuan (Universal Publishers, 2024)
This study aimed to evaluate the determinant factors of willingness to share the waqf information among Malaysian. The study investigates the impact of trust, reciprocity, power, life satisfaction and commitment as independent factors on the willingness of waqf stakeholders in Malaysia to share information. Design/methodology/approach: This study adopts a quantitative research approach, utilising the information sharing theory. The analysis employs the SPSS software to analyse the demographic factor for descriptive analysis and partial least square structural equation modelling (PLS-SEM) using SMART PLS4 for hypotheses testing. The study was conducted between April until August 2023, involving 370 purposively sampled respondents who were Waqif, Mawquf Alaih, or possessed knowledge about endowing waqf. The study intends to demonstrate the validity of factors influencing waqf stakeholders' willingness to share information, thereby enhancing Malaysia's waqf co-creation ecosystem. Findings: The result show that power, life satisfaction and commitment positively significant with the willingness to share the waqf information. Meanwhile, trust and reciprocity do not appear significantly influence the willingness to share the waqf information. Research limitations/implications: Given that the current study relied solely on questionnaires for data collection, a qualitative approach (interviews) should be incorporated to provide in-depth data. As the respondents were limited to the public, data from waqf institutions should also be collected to gain a more comprehensive perspective and generate new ideas to increase a person’s willingness to share waqf information among Malaysian. Practical implications: This study contributes significantly to the current literature concerning the willingness to share the waqf information. Policy makers encourage to develop of stakeholder-oriented strategy to promote power, life satisfaction and commitment to increase the willingness of waqf to share information. Aside from that, waqf institutions need to improve the waqf trust and reciprocity. The study offers empirical insights, bridging the gap between theory and practice in building trust and improving waqf contribution among stakeholders. These findings can influence the economic impact through policy implications. Society's willingness to share waqf information significantly impact fund sustainability. Increased waqf contributions can drive substantial projects, benefiting society and improving overall quality of life. Originality/value: to the best of authors’ knowledge, this is among the first comprehensive empirical studies that examine the willingness to share information focusing on the waqf area. Thus, the findings offer a valuable contribution to the waqf institutions to strategise and improvement the waqf sustainability